2011
DOI: 10.1136/tobaccocontrol-2011-050280
|View full text |Cite
|
Sign up to set email alerts
|

Women and tobacco: a call for including gender in tobacco control research, policy and practice

Abstract: Objectives Female smoking is predicted to double between 2005 and 2025. There have been numerous calls for action on women's tobacco use over the past two decades. In the present work, evidence about female tobacco use, progress, challenges and ways forward for developing gendered tobacco control is reviewed. Methods Literature on girls, women and tobacco was reviewed to identify trends and determinants of tobacco use and exposure, the application of gender analysis, tobacco marketing, the impact of tobacco co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
206
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(227 citation statements)
references
References 71 publications
11
206
0
10
Order By: Relevance
“…One major strength of this study is the relatively large sample size, which results in findings representative of the female population of Korea. This accords with the findings of a prior study, in which the prevalence of smoking among females in high-income countries was found to be declining (Amos et al, 2012). Nevertheless, elevated prevalence of inaccurate self-reports by females remained present in our sample.…”
Section: Discussionsupporting
confidence: 93%
“…One major strength of this study is the relatively large sample size, which results in findings representative of the female population of Korea. This accords with the findings of a prior study, in which the prevalence of smoking among females in high-income countries was found to be declining (Amos et al, 2012). Nevertheless, elevated prevalence of inaccurate self-reports by females remained present in our sample.…”
Section: Discussionsupporting
confidence: 93%
“…The main explanations for these trends are the empowerment of women and the decline in gender inequality in western societies (Hitchman and Fong 2011). Accordingly, a number of studies have pointed to the urgent need to include women in the target populations of campaigns aimed at discouraging the consumption of these substances (Amos et al 2011). …”
Section: Tobacco and Alcohol Consumptionmentioning
confidence: 99%
“…Ankara kent merkezinde bir kurumda yapılan çalışmada görüşülen kadınların öğrenim düzeyleri yüksek olmasına karşılık tütün endüstri-sinden etkilendikleri görülmektedir. Diğer taraftan gelişmekte olan ülkelerde olduğu gibi ülkemizde de sigara kullanımı kadınlar arasında giderek daha popüler hale gelmektedir [27]. Araştırmanın sonuçları da kadınlardaki sigara kullanım-daki artışı destekler niteliktedir.…”
Section: Discussionunclassified